Understanding the role of amyloid on cerebral microvasculature in Alzheimer's disease: A pre‐clinical Intra Voxel Incoherent Motion (IVIM) study. (20th December 2022) - Shahid, Syed Salman; Yen, Jui‐Hung; Paraiso, Hallel C; Wu, Yu‐Chien; Yu, Ivorine
Abstract: Background: Vascular perturbation is emerging as an important contribution to Alzheimer's disease (AD) trajectory. However, the role of microvascular alterations in pathophysiological processes remains unclear. We hypothesized a direct link between β‐amyloid (Aβ) and the cerebral microvasculature, leading to vascular stress, deteriorated blood‐brain barrier, and impaired microcirculation. The early detection of changes in the microvasculature can be used as an early biomarker to study underlying disease mechanisms. This study used intra‐voxel incoherent motion (IVIM) technique to quantitatively map functional capillaries related to blood volume fraction as surrogate marker for microvasculature alterations in an Alzheimer's disease mouse model. Method: Male 5xFAD mice at 6‐months‐old and age‐matched littermates were scanned using high‐resolution IVIM optimized DWI. The DWI and anatomical images were acquired on a horizontal bore 9.4T Biospec micro‐MRI system equipped with a 1 H cryogenic coil. 2D T2‐weightd images were acquired with a voxel size of 60x60x300 µm 3 and DWIs were acquired with a voxel size of 120x120x300 µm 3 . Hippocampal subfields (CA1, CA2, CA3, DG, and Subiculum) in (Badhwar hippocampal) atlas space were transformed to individual T2W space and then linearly transformed to DWI space. IVIM maps (Apparent diffusion coefficient [D], pseudo‐diffusion coefficient [D * ], and perfusion fraction [fIVIM ]) were calculated (voxel‐wise) using a bi‐exponential IVIM model. The mean fIVIM of individual subfields were used for group‐wise comparison, and the Hedges'g were used for effect‐size analysis. Result: Our preliminary results showed regional differences in microvascular perfusion fraction between control (n=6) and 5xFAD (n=8) mice at 6 months of age. fIVIM was significantly lower in DG (p<0.05; Hedge's g =‐1.4; 95% CI: ‐2.552, ‐0.202) and in Subiculum (p<0.05; Hedge's g=‐1.3; 95% CI: ‐2.54, ‐0.194) of 5xFAD compared to wild‐type mice. The fIVIM remains unchanged in other subfields. The decreased fIVIM suggested that deficits in the capillary network of DG and Subiculum develop early Conclusion: These findings support the sensitivity of IVIM to detect circulatory deficits in the hippocampal microvasculature associated with Aβ pathology. The IVIM may provide new insight into cerebral small vessel health in an early AD stage without a contrast agent administration and can be readily translated to the clinic.